Cannabis-based medicines and pain: a review of potential synergistic and entourage effects - Anand,U; Pacchetti,B; Anand,P; Sodergren,MH (Pain Management, 2021)
The recent legalization of medicinal cannabis in several jurisdictions has spurred the development of therapeutic formulations for chronic pain. Unlike pure delta-9-tetrahydrocannabinol (THC), full-spectrum products contain naturally occurring cannabinoids and have been reported to show improved efficacy or tolerability, attributed to synergy between cannabinoids and other components in the cannabis plant. Although ‘synergy’ indicates that two or more active compounds may produce an additive or combined effect greater than their individual analgesic effect, potentiation of the biological effect of a compound by related but inactive compounds, in combination, was termed the ‘entourage effect’. Here, we review current evidence for potential synergistic and entourage effects of cannabinoids in pain relief. However, definitive clinical trials and in vitro functional studies are still required.